Isorhamnetin Enhances the Radiosensitivity of A549 Cells Through Interleukin-13 and the NF-κB Signaling Pathway - Du, Yarong; Jia, Cong; Liu, Yan; Li, Yehua; Wang, Jufang; Sun, Kun (Frontiers in Pharmacology, 2021)
Isorhamnetin (ISO), a naturally occurring plant flavonoid, is widely used as a phytomedicine. The major treatment modality for non-small-cell lung carcinoma (NSCLC) is radiotherapy. However, radiotherapy can induce radioresistance in cancer cells, thereby resulting in a poor response rate. Our results demonstrated that pretreatment with ISO induced radiosensitizing effect in A549 cells using colony formation, micronucleus, and γH2AX foci assays. In addition, ISO pretreatment significantly enhanced the radiation-induced incidence of apoptosis, the collapse of mitochondrial membrane potential, and the expressions of proteins associated with cellular apoptosis and suppressed the upregulation of NF-κBp65 induced by irradiation in A549 cells. Interestingly, the expression of interleukin-13 (IL-13), an anti-inflammatory cytokine, was positively correlated with the ISO-mediated radiosensitization of A549 cells. The knockdown of IL-13 expression by RNA interference decreased the IL-13 level and thus reduced ISO-mediated radiosensitivity in cells. We also found that the IR-induced NF-κB signaling activation was inhibited by ISO pretreatment, and it was abrogated in IL-13 silenced cells. We speculated that ISO may confer radiosensitivity on A549 cells via increasing the expression of IL-13 and inhibiting the activation of NF-κB. To our knowledge, this is the first report demonstrating the effects of ISO treatment on the responsiveness of lung cancer cells to irradiation through IL-13 and the NF-κB signaling pathway. In summary, ISO is a naturally occurring radiosensitizer with a potential application in adjuvant radiotherapy.